"I buy it, but how do we pull it off?": A structured process for teacher candidates' interdisciplinary curriculum development. Issue 5 (19th October 2020) - Dack, Hilary
Abstract: This We Believe advocates the use of a curriculum that maximizes early adolescent learning by integrating multiple disciplines rather than teaching them in isolation. The development of an interdisciplinary curricular unit is a common assignment in middle grades teacher education programs that seek to prepare teacher candidates to undertake this curricular approach in their future careers. However, this common assignment presents challenges to both the instructors who design the project and the candidates who undertake it. This article offers middle-level teacher educators a structured process that guides candidates' development of a high-quality interdisciplinary unit through clear and intentionally sequenced steps that are rigorous but approachable.